2007
DOI: 10.1021/nl0708922
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Half-Metallicity in Edge-Oxidized Zigzag Graphene Nanoribbons

Abstract: We present a novel comprehensive first-principles theoretical study of the electronic properties and relative stabilities of edge-oxidized zigzag graphene nanoribbons. The oxidation schemes considered include hydroxyl, carboxyl, ether, and ketone groups. Using screened exchange density functional theory, we show that these oxidized ribbons are more stable than hydrogen-terminated nanoribbons except for the case of the etheric groups. The stable oxidized configurations maintain a spin-polarized ground state wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
497
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 564 publications
(527 citation statements)
references
References 66 publications
27
497
2
1
Order By: Relevance
“…This conclusion is in striking difference from the case of ZZ-GNRs, where the ground electronic state was found to have an AFM spin ordering regardless of the dimensions of the ribbon. [19][20][21][22][23][24][25][26]28,29,42,[45][46][47][48][49][50][51][52] Interestingly, contradicting results have been reported in the literature, 33 indicating that the ground state of unpassivated zigzag CNTs has a low-spin AFM ordering even for nanotubes that have earlier been considered to present a high-spin ferromagnetically ordered ground state. 32 In light of the considerable progress that has been made in the synthesis and fabrication of ultra-short [60][61][62][63][64] and open ended 65 CNTs and ultra-narrow GNRs, [66][67][68][69] it is desirable to obtain a full understanding of their electronic properties.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…This conclusion is in striking difference from the case of ZZ-GNRs, where the ground electronic state was found to have an AFM spin ordering regardless of the dimensions of the ribbon. [19][20][21][22][23][24][25][26]28,29,42,[45][46][47][48][49][50][51][52] Interestingly, contradicting results have been reported in the literature, 33 indicating that the ground state of unpassivated zigzag CNTs has a low-spin AFM ordering even for nanotubes that have earlier been considered to present a high-spin ferromagnetically ordered ground state. 32 In light of the considerable progress that has been made in the synthesis and fabrication of ultra-short [60][61][62][63][64] and open ended 65 CNTs and ultra-narrow GNRs, [66][67][68][69] it is desirable to obtain a full understanding of their electronic properties.…”
Section: Introductionmentioning
confidence: 93%
“…Unlike previous reports on these systems, 32,37 we find that all zigzag CNTs studied present an antiferromagnetically ordered ground state, regardless of their diameter and length. Furthermore, as is the case with infinitely long [45][46][47] and finite 52 GNRs, the application of an external axial electric field results in half-metallic behavior.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…[16][17][18][19] It is of great importance to develop optimized electrode materials based on graphene which combine both the intrinsic high charge carrier conductivity and chemical stability in aqueous solutions. It is widely reported that functionalized graphene nanoribbons can speed/hinder charge carrier exchange and hence affect the overall performance of electrodes used in diverse electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%